Penerjemahan Item Spesifik Budaya Dalam To Kill A Mockingbird Karya Harper Lee - Barathayomi, Wieka (Kementerian Sekretariat Negara Republik Indonesia, 2016)
This study aims to find out the translation strategies used by the translator to translate cultural specific items in Harper Lee’s To Kill a Mockingbird. The sources of the data are taken from Harper Lee’s To Kill a Mockingbird and its translation. The research procedure consists of reading the whole text, identifying cultural specific items, and analyzing the translation strategies used by the translator to translate cultural specific items. The study results show that the translator used four main strategies to translate cultural specific items, namely loan words, loan words plus explanation, additional information, and generic words. Keywords: translation strategy, research procedure, cultural-specific item.